The implementation of finite state automata in government SMS services (MySMS) - Nik Ab Aziz, Nik Sakinah; Mohd Sani, Nor Fazlida; Othman, Rozaini; Othman, Haslila (American-Eurasian Network for Scientific Information, 2015)
Mobile SMS is a growing technology that integrates mobile technology with information system. Government and its clients also benefited from this technology. However, we need to provide good management of the system to lower the risks such as due to network bottleneck or congestion. Non-deterministic Finite Automata (NFA)model is proposed to design the system flow and prove that the system is executed correctly with the developed NFA model.